Investigating the impact of pedoclimatic conditions on the oenological performance of two red cultivars grown throughout southern Italy - Iorizzo, Massimo; Sicilia, Angelo; Nicolosi, Elisabetta; Forino, Martino; Picariello, Luigi; Lo Piero, Angela Roberta; Vitale, Andrea; Monaco, Eugenia; Ferlito, Filippo; Succi, Mariantonietta; Tremonte, Patrizio; Gambuti, Angelita; et al. (Frontiers in Plant Science, 2023)
The cultivated grapevine, Vitis vinifera subsp. vinifera, possesses a rich biodiversity with numerous varieties. Each variety adapts differently to varying pedoclimatic conditions, which greatly influence the terroir expression of wine regions. These conditions impact vine growth, physiology, and berry composition, ultimately shaping the unique characteristics and typicity of the wines produced. Nowadays, the potential of the different adaptation capacities of grape varieties has not yet been thoroughly investigated. We addressed this issue by studying two grape varieties, Aglianico and Cabernet Sauvignon, in two different pedoclimatic conditions of Southern Italy. We evaluated and compared the effect of different pedoclimatic conditions on plant physiology, the microbial quality of grapes using Next-Generation Sequencing (NGS) technology, the expression trends of key genes in ripe berries and the concentration of phenolic compounds in grapes and wines by HPLC-MS, HPLC-DAD, NMR and spectrophotometric analyses. Metabolomic and microbiome data were integrated with quantitative gene expression analyses to examine varietal differences and plasticity of genes involved in important oenological pathways. The data collected showed that the phenotypic response of studied grapes in terms of vigor, production, and fruit quality is strongly influenced by the pedoclimatic 2 conditions and, in particular, by soil physical properties. Furthermore, Aglianico grape variety was more influenced than the Cabernet Sauvignon by environmental conditions. In conclusion, the obtained findings not only reinforce the terroir concept and our comprehension of grape's ability to adapt to climate variations but can also have implications for the future usage of grape genetic resources.